Contabilidade Internacional - análise dos periódicos internacionais sobre pesquisas em educação contábil face à convergência e globalização - Gilson Cella (Revista Contemporânea de Contabilidade, 2011)
The differences between the accounting practices have been gradually harmonized through a set of high-quality accounting standards and public interest, which is one of the goals of the International Accounting Standards Board (IASB), through the publication of International Financial Reporting Standards (IFRS). In this context of convergence of international and local convergence, and changes caused by globalization of financial reporting, the training of accountants is presented as a concern of international accounting organi-zations, encouraging educational institutions to adapt to these changes. The aim of this paper is to analyze international accounting journals to see which are the subjects of research in accounting education in the face of globalization and convergence of financial reporting. The results showed that there are three most common themes in the polls: continuing education of the accounting, harmonization and convergence of international accounting, and subjects for research in accounting.